Valley dynamics of different excitonic states in monolayer WSe2 grown by molecular beam epitaxy. (1st August 2022) - Hu, Shengmin; Ye, Jialiang; Liu, Ruiqi; Zhang, Xinhui
Abstract: Monolayer transition-metal dichalcogenides possess rich excitonic physics and unique valley-contrasting optical selection rule, and offer a great platform for long spin/valley lifetime engineering and the associated spin/valleytronics exploration. Using two-color time-resolved Kerr rotation and time-resolved reflectivity spectroscopy, we investigate the spin/valley dynamics of different excitonic states in monolayer WSe2 grown by molecular beam epitaxy. With fine tuning of the photon energy of both pump and probe beams, the valley relaxation process for the neutral excitons and trions is found to be remarkably different—their characteristic spin/valley lifetimes vary from picoseconds to nanoseconds, respectively. The observed long trion spin lifetime of > 2.0 ns is discussed to be associated with the dark trion states, which is evidenced by the photon-energy dependent valley polarization relaxation. Our results also reveal that valley depolarization for these different excitonic states is intimately connected with the strong Coulomb interaction when the optical excitation energy is above the exciton resonance.